Effects of supplementing protease in low protein and low energy diets on growth performance and physiological responses of broiler chicken under different environmental conditions - Law, Elizabeth Fang Lin (2018)
Protein and energy are two important cost determinants in poultry diet’s formulation. There is a great of interest in the use of low crude protein (CP) and/or metabolisable energy (ME) diets for feed cost saving. However, the diet may negatively affect the broilers performance. Proteases have been proven to improve nutrient digestibility and performance of broilers fed low CP diets. However, the ability of nutrient digestibility of proteases is inconsistence and depends on types of proteases used. Furthermorre, none of the study reported protease supplementation improved nutrient digestibility and performance of broilers fed low-CP and/or low-ME diets under stressful condition. Hence, four studies were conducted to access the effects of two different proteases (EA and EB) on nutrient digestibility of low CP feed and to evaluate the effects of CP and or ME reduction with supplemental protease on growth performance and physiological responses of broilers under natural environment, heat stress (HS) and high stocking density (SD) conditions. The objective of experiment one (Chapter 3) was to evaluate effects of two commercial endopeptidase proteases (EA and EB) on apparent ileal digestible energy (AIDE), CP and amino acids (AA) of diet in broilers fed on either recommended-CP (CP19) or low-CP (CP16) diets. Diets with recommended- CP had higher AIDE (P<0.001), CP (P<0.001) and AA (P<0.05) digestibility than those of low-CP diets irrespective of protease supplementation. Proteases EA (CibenzaTM DP100; Novus International Inc., USA) improved AIDE (P=0.003), CP (P=0.004), and majority of AA (P<0.005) digestibility in broiler chickens but not protease EB (Ronozyme®ProAct; DSM Nutritional Products Ltd, Switzerland) compared to control regardless of dietary protein levels. Hence, protease EA was used for the following experiments (Chapter 4, 5 and 6). Experiment 2 (Chapter 4) was conducted to investigate the effects of reducing CP (21.0%,19.7%, 18.5% and 17.2% from 1-21 days and 19.0%, 17.9%, 16.7%,and 15.6% from 22 to 35 days, respectively) with endopeptidase protease EA supplementation on growth performance, serum metabolites, carcass traits, small intestinal morphology and endogenous protease activity in broiler chickens under the natural tropical environment. Reducing CP linearly reduced weight gain (WG) (P<0.001), serum albumin (P<0.001), total protein (P<0.001) and carcass traits (P<0.005) and increased feed conversion ratio (FCR) (P<0.001), serum triglycerides (P<0.005) and adipose fat (P<0.001). There was no adverse effect of reducing dietary CP on morphological parameters of the intestine (P>0.005) and on the pancreatic (P>0.005) and small intestinal (P>0.005) digesta endogenous protease activity. Protease supplementation improved FCR (P<0.005), WG (P<0.005), carcass yield (P<0.005) and intestinal absorptive surface area (P<0.005). Following the optimization of nutritional factor in previous two experiment (chapter 3 and 4), it is necessary to answer the question whether the same nutritional condition is affected by various environmental factors such as high ambient temperature (Chapter 5) and high stocking density (Chapter 6). Experiment 3 (Chapter 5) was conducted to investigate the effect of low CP and/or ME with supplemental protease on the growth performance, corticosterone (CORT), acute phase proteins (APP), heat shock protein (HSP) 70, adipose fat and breast meat yield of broilers under low and HS conditions. Regardless of protease supplementation, both dietary CP and ME could be reduced to 18.5% and 2985 kcal/kg, respectively without any adverse effects on feed intake (FI) (P>0.005), WG (P>0.005) and mortality in broilers during starter (d 1-21) period. However, either CP or ME could be reduced during finisher (d 22-42) period. Reduction of both dietary CP and ME was detrimental to FCR (P<0.005) although breast meat yield (P>0.005) was not affected. Irrespective of dietary CP and ME, supplementation of protease had negligible influence on growth performance (P>0.005). Protease reduced adipose fat in broilers fed low-ME diets. Heat stress adversely affects the growth performance (P<0.005), breast meat yield (P<0.005), serum metabolites (P<0.001), CORT (P<0.001) and APP (P<0.005) of broiler chickens regardless of protease supplementation, dietary CP or ME. Experiment 4 (Chapter 6) was conducted to investigate the effects of protease supplementation in low-CP diet during the finisher period on growth performance, pododermatitis, immune response, physiological stress responses and cecal microfloral counts in broiler chickens under normal and high stocking densities. Results demonstrated that low-CP and low-ME diets could be fed to broilers during the starter period without detrimental effects on FCR (P>0.005) but negatively affected the antibody production against ND vaccination (P<0.001) later in life. Supplementing protease to low-CP diet during the finisher period had only a negligible effect on the performance (P>0.005) and immunity (P>0.005) of broiler chickens. However, cecal Clostridium population was reduced (P<0.001) following protease supplementation. High-SD was detrimental to growth performance (P<0.005), antibody production (P<0.001) and pododermatitis (P<0.001) in broiler chickens. In conclusion, dietary protein can be reduced to 18.5% and 16.7% during starter and finisher periods, respectively. However, ME could only be reduced to 2985 kcal/kgduring starter period but not during finisher period. There was little evidence that dietary addition of protease was consistently beneficial to broiler chickens fed low CP diets. Endopeptidase protease and dietary protein levels can independently affect the AIDE, CP, and AA digestibility in broiler chickens. Overall, the effects of endopeptidase protease suplementation in broilers fed low-CP diets were significant during the starter period. However, the significant effects were not appearant during the finisher period. In addition, growth performance and physiological reponses of broiler chickens can be affected by reducing CP and ME (nutritional factors) and environment challenges (high ambient temperature and high stocking density).